2000
DOI: 10.1592/phco.20.19.1441.34851
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Pharmacokinetics of Citalopram in Young and Elderly Subjects

Abstract: The pharmacokinetics and tolerability of citalopram in elderly subjects are similar to those observed in younger subjects. The slight differences observed in the elderly likely reflect declining liver and kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
5
29
0
1
Order By: Relevance
“…At this concentration (10 −6 mol/L), each pharmacologic agent (Atlanta Biologicals, Norcross, Georgia) was added to a separate aliquot of 4 × 10 −6 PBMCs/4 mL RPMI 1640 plus 10% fetal bovine serum (FBS). These ex vivo concentrations are consistent with steady state plasma concentrations in individuals taking citalopram and RU486, the two licensed drugs (57)(58)(59)(60). The next morning following the 18 hours incubation and within our 30-hour window, the natural killer cell assay was performed.…”
Section: Immune Assessmentsupporting
confidence: 66%
“…At this concentration (10 −6 mol/L), each pharmacologic agent (Atlanta Biologicals, Norcross, Georgia) was added to a separate aliquot of 4 × 10 −6 PBMCs/4 mL RPMI 1640 plus 10% fetal bovine serum (FBS). These ex vivo concentrations are consistent with steady state plasma concentrations in individuals taking citalopram and RU486, the two licensed drugs (57)(58)(59)(60). The next morning following the 18 hours incubation and within our 30-hour window, the natural killer cell assay was performed.…”
Section: Immune Assessmentsupporting
confidence: 66%
“…The clearance of drugs that undergo phase II metabolism [e.g., mizolastine (Lebrun-Vignes et al, 2001)] is unchanged in old age, whereas drugs that undergo phase I metabolism [e.g., ropinirole (Kaye and Nicholls, 2000), citalopram (Gutierrez and Abramowitz, 2000), rabeprazole (Swan et al, 1999), argatroban (Swan and Hursting, 2000)] have reduced clearance in older people. On the other hand, a review of pharmacokinetics found that aging in volunteers and subjects with rheumatoid arthritis was not associated with any significant change in cyclosporin pharmacokinetics; although, clearance was lower in older renal transplant recipients (Kovarik and Koelle, 1999).…”
Section: In Vitro Studies Of Aging and Hepatic Drug-metabolizing Enzymentioning
confidence: 99%
“…For the Cl t of citalopram a range of 367-545 mL/min (arithmetic mean ± standard deviation) has been estimated during pre-clinical trials [15][16][17] which can be used to calculate a range within which 68 % of all drug plasma concentrations are expected in a "normal" patient under medication with a given dose of the drug [13]: c max = D/Cl t max ; c min = D/Cl t min. The term "normal patient" refers to the study population of the phase II clinical trials in which pharmacokinetic parameters of a drug are usually estimated.…”
Section: Calculation Of Dose-related Reference Range Of Citaloprammentioning
confidence: 99%